Pembuktian Tindak Pidana Penggelapan yang Dilakukan Aparatur Sipil Negara dalam KUHP (2023): Studi Putusan Nomor: 32/Pid.B/2026/Pn Kbu - Muhammad Ramadhan Ar Raasyid (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The objective of this research is to analyze the evidentiary system for the crime of embezzlement under Law Number 1 of 2023 concerning the Criminal Code and to examine the elements of proof found in Court Decision Number 32/Pid.B/2026/PN Kbu. This study employs a normative-juridical method, utilizing both case study and statutory approaches. The findings indicate that proving the crime of embezzlement requires at least two pieces of valid evidence accompanied by the judge's conviction. In the analyzed case, the elements of embezzlement under Article 486 of the Criminal Code were met; the defendant had taken possession of the victim's money, originally handed over legally for the specific purpose of securing a Civil Servant appointment, but subsequently committed an unlawful act by failing to use the funds as promised and failing to return the money to the victim. The defendant's modus operandi involved persuading the victim with an offer to facilitate their entry into the Civil Service, leading the victim to transfer funds in installments via bank transfers and direct cash payments. Based on evidence such as receipts, transfer records and witness testimonies, the victim suffered a financial loss of IDR 335,650,000. Consequently, it is concluded that the body of evidence demonstrates the fulfillment of the element regarding the possession of another person's property obtained through an unlawful act.